Traditional Chinese medicine prescription Guizhi Fuling Pills ameliorate cisplatin-induced renal injury via remodeling intestinal homeostasis in mice with tongue squamous cell carcinoma - Fu, Kai; Yin, Shaoning; Liu, Tengfei; Wang, Weiyi (Frontiers in Pharmacology, 2025)
IntroductionGuizhi Fuling Pills, a traditional Chinese medicine, may affect cisplatin-induced kidney damage during tongue squamous cell carcinoma (TSCC) treatment via the gut–kidney axis, but this is not well understood. This study explores the impact of Guizhi Fuling Pills on gut microbiota and intestinal barrier function, its protective effects against cisplatin-induced kidney injury, and the mechanisms involved.MethodsA tongue tumor model was created in nude mice using Cal27 cells. Treatments included cisplatin, Guizhi Fuling Pills, or both. Kidney function was evaluated through serum creatinine (CRE) and blood urea nitrogen (BUN). Oxidative stress and inflammation were assessed by measuring malondialdehyde (MDA), superoxide dismutase (SOD) activity, and tumor necrosis factor-α (TNF-α). Gut microbiota was analyzed via 16S rRNA sequencing, and intestinal morphology was examined using H&E and PAS staining.ResultsThe coadministration of Guizhi Fuling Pills with DDP demonstrated multifaceted effects. At the systemic level, it ameliorated renal pathological changes, as evidenced by decreased serum levels of CRE, BUN, MDA, and TNF-α, alongside increased SOD activity. It also enhanced the inhibitory effect on TSCC tumor growth. In the gut, this combination reduced crypt depth, increased goblet cell number, and favorably modulated the microbiota by decreasing the abundance of Desulfovibrioand increasing beneficial bacteria including Lactobacillus, Kineothrix, and Eubacterium, without affecting ZO-1 expression.DiscussionGuizhi Fuling Pill effectively mitigates cisplatin-induced renal injury and maintains its anti-tumor efficacy in TSCC by modulating gut microflora and reducing inflammation.